Highly resistive and highly corrosion-resistant ceramic materials and wafer support
A ceramic material with magnesium-aluminum oxynitride and controlled carbon content addresses corrosion and resistivity issues in semiconductor manufacturing, enabling reliable wafer adsorption and reduced leakage currents at high temperatures.
Patent Information
- Application Number
- JP2022042036
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-03-17
- Publication Date
- 2025-02-12
- Estimated Expiration
- 2042-03-17
AI Technical Summary
Semiconductor manufacturing equipment requires materials with high corrosion resistance and increased volume resistivity at high temperatures to withstand reactive halogen-based plasmas and electrostatically adsorb wafers effectively.
A ceramic material containing magnesium-aluminum oxynitride with a carbon content of 0.005-0.275% by mass, which provides sufficient corrosion resistance and high volume resistivity, is used to form a wafer mounting table with integrated electrodes and thermal conductivity substrates.
The ceramic material ensures effective corrosion resistance and high volume resistivity, allowing reliable electrostatic adsorption and reduced leakage currents at high temperatures, while maintaining thermal conductivity for uniform wafer temperature.
Smart Images

Figure 0007628979000003 
Figure 0007628979000004 
Figure 0007628979000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a highly resistive and highly corrosion resistant ceramic material and a wafer support. [Background technology]
[0002] In semiconductor manufacturing equipment used in dry processes and plasma coating in semiconductor manufacturing, highly reactive halogen-based plasma such as F and Cl is used for etching and cleaning. For this reason, members assembled in such semiconductor manufacturing equipment are required to have high corrosion resistance. As shown in Patent Document 1, a ceramic material having a magnesium-aluminum oxynitride phase as the main phase is known as a material having high corrosion resistance. This ceramic material can withstand the highly reactive halogen-based plasma used in the semiconductor manufacturing process for a long period of time. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 5680645 Summary of the Invention [Problem to be solved by the invention]
[0004] In recent years, the process temperature has been increasing (500°C or higher) to generate high-quality films, so not only is there a need for sufficient corrosion resistance at high temperatures, but the ability to electrostatically adsorb wafers at high temperatures is also required.
[0005] The present invention has been made to solve such problems, and a main object of the present invention is to provide a material having sufficient corrosion resistance at high temperatures and also having a high volume resistivity at high temperatures. [Means for solving the problem]
[0006] The highly resistive and highly corrosion resistant ceramic material of the present invention is A ceramic material containing magnesium-aluminum oxynitride, Carbon content is 0.005 to 0.275% by mass It is of the following.
[0007] This ceramic material contains carbon in an appropriate range, and therefore has sufficient corrosion resistance at high temperatures and can have a high volume resistivity at high temperatures.
[0008] The wafer mounting table of the present invention comprises: A ceramic base formed of the above-mentioned ceramic material and capable of mounting a wafer on its upper surface; An electrode disposed inside the ceramic substrate; Is it equipped with A ceramic base formed of the above-mentioned ceramic material and capable of mounting a wafer on its upper surface; a highly thermally conductive base provided on a lower surface of the ceramic base and having a thermal conductivity higher than that of the ceramic base; an electrode disposed inside the ceramic base, inside the highly thermally conductive base, or between the ceramic base and the highly thermally conductive base; The highly thermally conductive substrate Of a resistance heating element disposed below the electrodes; It is equipped with the following:
[0009] According to such a wafer mounting table, since the ceramic base is made of the above-mentioned ceramic material, it has sufficient corrosion resistance at high temperatures and can increase the volume resistivity at high temperatures. Here, the "electrode" may be, for example, an electrostatic electrode, a heater electrode (resistance heating element), or a radio frequency (RF) electrode for generating plasma. [Brief description of the drawings]
[0010] [Figure 1] FIG. [Diagram 2] FIG. [Diagram 3]FIG. [Figure 4] FIG. [Diagram 5] 1 is an XRD chart of Experimental Example 3. [Figure 6] 1 is an XRD chart of Experimental Example 5. [Figure 7] Graph showing the relationship between C content and volume resistivity at 500°C. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] A preferred embodiment of the present invention will be described below with reference to the drawings. FIGS. 1 to 4 are vertical cross-sectional views of wafer mounting tables 10 to 40. In this specification, "upper" and "lower" do not indicate an absolute positional relationship, but rather a relative positional relationship. Therefore, depending on the orientation of the wafer mounting tables 10 to 40, "upper" and "lower" can become "lower" and "upper", "left" and "right", or "front" and "rear". In this specification, "-" indicating a numerical range is used to mean that the numerical values before and after it are included as the lower and upper limits.
[0012] The high resistance and high corrosion resistance ceramic material of this embodiment contains magnesium-aluminum oxynitride and has a carbon content of 0.005 to 0.275 mass%. If the carbon content is within this range, the ceramic material has sufficient corrosion resistance at high temperatures and can increase the volume resistivity at high temperatures. For example, when this ceramic material is used in a ceramic base having an electrostatic electrode with a wafer mounting surface, it is possible to electrostatically adsorb a wafer at high temperatures and suppress leakage current flow between the wafer and the electrode when the wafer is processed at high temperatures. In addition, when this ceramic material is used in a ceramic base having a heater electrode (resistance heating element) or an RF electrode, it is possible to suppress leakage current flow between the wafer and the electrode when the wafer is processed at high temperatures. When the carbon content is less than 0.005 mass% or more than 0.275 mass%, the volume resistivity at 500°C is low. The carbon content is preferably 0.005 to 0.21 mass%. The ceramic material of this embodiment preferably contains magnesium-aluminum oxynitride as a main phase. Here, the main phase refers to the phase that is contained in the greatest amount among all phases.
[0013] The ceramic material of this embodiment has a volume resistivity of 1×10 at 500° C. 9 It is preferable that the volume resistivity at 500°C is Ωcm or more. 1 ×10 9 If the ceramic material has a resistivity of Ωcm or more, when the ceramic material is used as a ceramic base with a built-in electrode having a wafer mounting surface, leakage current between the wafer and the electrode during wafer processing at high temperatures can be sufficiently suppressed. Furthermore, when the ceramic material is used as an electrostatic chuck, the wafer can be electrostatically attracted reliably at high temperatures by the Johnsen-Rahbek force. Furthermore, when the volume resistivity at 500°C is 5×10 11 It is preferable that the resistivity is Ωcm or less. In this way, when this ceramic material is used for an electrostatic chuck, the wafer adsorption / desorption response can be improved.
[0014] The ceramic material of this embodiment may contain titanium. By containing titanium, the color of the ceramic material can be made black. Therefore, color unevenness of the ceramic material can be made less noticeable. The titanium content may be set so that the corrosion resistance is not reduced and the volume resistivity at 500°C does not deviate from the above-mentioned range, for example, in the range of 0.1 to 1 mass% in terms of oxide.
[0015] The ceramic material of the present embodiment preferably has a magnesium-aluminum oxynitride phase as its main phase, which has an XRD peak at 2θ=47-50° (preferably 47-49°) when CuKα radiation is used. Such ceramic materials are preferable because they have corrosion resistance to halogenated plasma equal to or higher than that of spinel. This main phase preferably coincides with the peak of the magnesium-aluminum oxynitride according to Patent Document 1 (Japanese Patent No. 5680645). Note that the peak of the magnesium-aluminum oxynitride according to Patent Document 1 does not coincide with the peak of MgAlON (or Magalon) shown in, for example, Reference Document 1 (J. Am. Ceram. Soc., 93[2] 322-325(2010)) or Reference Document 2 (JP Patent Publication 2008-115065). In general, these MgAlONs are known as spinels in which N components are dissolved, and are considered to have a different crystal structure from the magnesium-aluminum oxynitride according to Patent Document 1.
[0016] Next, a manufacturing example of the ceramic material of this embodiment will be described. The ceramic material of this embodiment can be manufactured by molding and firing a mixed powder of magnesium oxide, alumina, aluminum nitride, and a carbon source. For example, magnesium oxide is weighed out so that it is 5 mass% or more and 60 mass% or less, alumina is 60 mass% or less, and aluminum nitride is 90 mass% or less, and a carbon source is further added to these, and the mixed powder is molded and fired. As the carbon source, an organic binder or an organic dispersant may be added, or carbon powder may be added. The amount of the carbon source added may be set so that the carbon content contained in the ceramic material after firing is 0.005 to 0.2 mass%. Alternatively, the carbon content may be adjusted so that the carbon content contained in the ceramic material after firing is 0.005 to 0.2 mass% by degreasing at a stage before firing. In this case, the carbon content may be adjusted by the degreasing temperature. The degreasing temperature is preferably set in the range of, for example, 300 to 600°C. For example, the molding may be performed by granulating a slurry of the mixed powder to form granules, and then powder pressing the granules, or by forming the slurry of the mixed powder into a green sheet by a doctor blade method. The pressure during molding is not particularly limited, and may be appropriately set to a pressure at which the shape can be maintained. The firing temperature is preferably 1750°C or higher, and more preferably 1800 to 1950°C. In addition, the firing is preferably performed by hot press firing, and the pressing pressure during hot press firing is 50 to 300 kgf / cm. 2 The atmosphere during firing is preferably an atmosphere that does not affect the firing of the oxide raw material, and is preferably an inert atmosphere such as a nitrogen atmosphere, an argon atmosphere, or a helium atmosphere. The pressure during molding is not particularly limited and may be set appropriately to a pressure at which the shape can be maintained.
[0017] Next, the wafer mounting tables 10 to 40 will be described with reference to the drawings.
[0018] As shown in FIG. 1, the wafer mounting table 10 is an electrostatic chuck heater including an electrostatic electrode 14 disposed inside a ceramic base 12 and a resistance heating element 16 disposed inside the ceramic base 12 and below the electrostatic electrode 14.
[0019] The ceramic base 12 is a disk-shaped ceramic material formed from the above-mentioned ceramic material, and has a wafer mounting surface 12a on its upper surface on which a wafer can be mounted.
[0020] The electrostatic electrode 14 is a disk-shaped metal plate or metal mesh, and is provided parallel to the wafer mounting surface 12a. The electrostatic electrode 14 may be in the form of a foil, punched metal, printed electrode, or the like, in addition to a disk-shaped metal plate or mesh. Note that "parallel" refers to being completely parallel, or may be considered to be parallel if it is not completely parallel but is within an allowable error range (e.g., tolerance). The portion of the ceramic base 12 above the electrostatic electrode 14 functions as a dielectric layer. When a DC voltage is applied to the electrostatic electrode 14, the wafer mounted on the wafer mounting surface 12a is attracted to the wafer mounting surface 12a by the Johnsen-Rahbek force (electrostatic force). Examples of materials used for the electrostatic electrode 14 include W, Mo, W-Mo alloys, and carbides thereof.
[0021] The resistance heating element 16 is wired from one end to the other end in a single stroke across the entire ceramic base 12 when viewed from above, and generates heat by passing a current between one end and the other end. For example, a linear conductor bent and wound into a coil can be used as the resistance heating element 16. The wire diameter of the resistance heating element 16 is preferably about 0.3 mm to 0.5 mm, and in the case of a coil shape, the winding diameter is preferably about 2 mm to 4 mm, and the pitch is preferably about 1 mm to 7 mm. Here, the "winding diameter" refers to the inner diameter of the coil constituting the resistance heating element 16. As the shape of the resistance heating element 16, various shapes such as a ribbon shape, a mesh shape, a coil spring shape, a sheet shape, and a printed electrode can be adopted in addition to the coil shape. Examples of materials used for the resistance heating element 16 include W, Mo, W-Mo alloys, and carbides thereof.
[0022] A cylindrical shaft 18 is bonded to the lower surface of the wafer mounting table 10. The bonding may be performed by, for example, sintering or by using a bonding agent (e.g., an inorganic bonding agent). The shaft 18 is preferably made of a material having a linear thermal expansion coefficient that is the same as or close to that of the ceramic base 12. The shaft 18 is preferably made of AlN-YAG. YAG is an yttrium aluminum garnet (Y3Al5O 12 AlN-YAG is an abbreviation for titanium. AlN-YAG may contain titanium, and the titanium content may be, for example, 0.1 to 1 mass % calculated as oxide. Addition of titanium makes the color of AlN-YAG black, making color unevenness of AlN-YAG less noticeable.
[0023] According to the above-described wafer mounting table 10, since the ceramic base 12 is made of the above-described ceramic material, it has the same effects as the above-described ceramic material, for example, sufficient corrosion resistance at high temperatures and high volume resistivity at high temperatures. In addition, it is possible to electrostatically attract the wafer at high temperatures and to suppress leakage current flow between the wafer and the electrostatic electrode 14 when processing the wafer at high temperatures. Furthermore, it is possible to suppress leakage current flow between the wafer and the resistance heating element 16 when processing the wafer at high temperatures.
[0024] 2 is an electrostatic chuck heater in which a highly thermally conductive base 23 incorporating a resistance heating element 26 is bonded to the lower surface of a ceramic base 22 incorporating an electrostatic electrode 24. The bonding may be performed by, for example, sintering or by using a bonding agent (for example, an inorganic bonding agent).
[0025] The ceramic base 22 is a disk-shaped ceramic material, and has a wafer mounting surface 22a on the upper surface of the ceramic base 22. The electrostatic electrode 24 is the same as the electrostatic electrode 14 described above, and therefore a description thereof will be omitted.
[0026] The highly heat-conductive substrate 23 has a higher thermal conductivity than the ceramic substrate 22. 22The linear thermal expansion coefficient of AlN-YAG is the same as or close to that of AlN-YAG. AlN-YAG may contain titanium, and the content of titanium may be, for example, 0.1 to 1 mass% in terms of oxide. Addition of titanium makes the color of AlN-YAG black, making color unevenness of AlN-YAG less noticeable.
[0027] The resistive heating element 26 is the same as the resistive heating element 16 described above, and therefore a description thereof will be omitted.
[0028] A cylindrical shaft 28 is joined to the lower surface of the wafer mounting table 20. The shaft 28 is the same as the shaft 18 described above, and therefore a description thereof will be omitted.
[0029] According to the above-described wafer mounting table 20, since the ceramic base 22 is made of the above-described ceramic material, it has the same effects as the above-described ceramic material, for example, sufficient corrosion resistance at high temperatures and high volume resistivity at high temperatures. In addition, it is possible to electrostatically attract a wafer at high temperatures and to suppress leakage current flow between the wafer and the electrostatic electrode 14 when the wafer is processed at high temperatures.
[0030] Furthermore, in the wafer mounting table 20, since the highly thermally conductive base 23 is bonded to the lower surface of the ceramic base 22, it is easier to make the temperature of the wafer mounted on the wafer mounting surface 22a uniform than in the wafer mounting table 10.
[0031] Furthermore, since the highly heat-conductive base 23 has a thermal expansion coefficient that is the same as or close to that of the ceramic base 22, it is unlikely to peel off from the ceramic base 22 even if the temperature is repeatedly increased and decreased.
[0032] 3 is similar to the wafer stage 20, except that the electrostatic electrode 24 is disposed at the interface between the ceramic base 22 and the highly thermally conductive base 23. The wafer stage 30 also provides the same effects as the wafer stage 20.
[0033] 4 is similar to the wafer mounting table 20, except that the electrostatic electrode 24 is built into the highly thermally conductive base 23, not into the ceramic base 22. The resistance heating element 26 is disposed below the electrostatic electrode 24. The wafer mounting table 40 also provides the same effects as the wafer mounting table 20. However, since the dielectric layer (the portion above the electrostatic electrode 24) of the wafer mounting table 40 is made up of the ceramic base 22 and the highly thermally conductive base 23, it is easier to adjust the wafer chucking force of the wafer mounting tables 10 to 30, whose dielectric layer is made up only of the ceramic base 22.
[0034] It goes without saying that the present invention is not limited to the above-described embodiment, and can be embodied in various forms within the technical scope of the present invention.
[0035] For example, although the wafer mounting tables 10 to 40 are exemplified as those having the built-in electrostatic electrodes 14, 24, the electrostatic electrodes 14, 24 may not be built in. Even in this case, it is possible to prevent leakage current from flowing between the wafer and the resistance heating elements 16, 26. Furthermore, RF electrodes may be built in instead of or in addition to the electrostatic electrodes 14, 24, and the electrostatic electrodes 14, 24 may also serve as RF electrodes.
[0036] In addition, the outer periphery (upper surface, side surface, and lower surface) of the highly heat-conductive base 23 can be wrapped with the above-mentioned ceramic material, thereby improving the corrosion resistance of the side surface and bottom surface. EXAMPLES
[0037] Examples of the present invention will be described below. Experimental Examples 2 to 6, 9 to 11, 13 to 15, and 17 to 19 correspond to the examples of the present invention. Note that the following examples do not limit the present invention in any way.
[0038] [Experimental Examples 1-7] Mixture In Experimental Example 1, the MgO raw material, the Al2O3 raw material, and the AlN raw material were weighed out to have the mass% shown in Table 1, and wet-mixed for 4 hours using isopropyl alcohol as a solvent, a nylon pot, and alumina balls with a diameter of 5 mm. After mixing, the slurry was taken out and dried at 110°C in a nitrogen stream. It was then passed through a 30-mesh sieve to obtain a mixed powder.
[0039] In Experimental Example 2, MgO raw material, Al2O3 raw material, and AlN raw material were weighed out to have the mass% shown in Table 1, and 1.0 mass% of an acrylic binder and 0.1 mass% of a polycarboxylic acid dispersant were added to isopropyl alcohol as a solvent, and the mixture was wet mixed in a trommel with alumina boulders for 4 hours to prepare a raw material slurry. The obtained raw material slurry was spray-dried using a spray dryer to prepare granules. The obtained granules were then heated in air at 500°C for 24 hours to prepare partially degreased granules.
[0040] In Experimental Example 3, granules were prepared in the same manner as in Experimental Example 2, except that they were partially degreased by heating in air at 500° C. for 5 hours.
[0041] In Experimental Example 4, granules were prepared in the same manner as in Experimental Example 2, except that 1.5% by mass of an acrylic binder and 0.5% by mass of a polycarboxylic acid dispersant were added and the granules were partially degreased by heating in air at 450°C for 5 hours.
[0042] In Experimental Example 5, granules were prepared in the same manner as in Experimental Example 4, except that degreasing was not carried out.
[0043] In Experimental Example 6, the MgO raw material, the Al2O3 raw material, and the AlN raw material were weighed out to have the mass% shown in Table 1, and were mixed in a nylon pot and alumina balls with a diameter of 5 mm for 4 hours using isopropyl alcohol as a solvent and 0.3 mass% of carbon powder added. After mixing, the slurry was taken out and dried at 110°C in a nitrogen stream. It was then passed through a 30 mesh sieve to obtain a mixed powder.
[0044] In Experimental Example 7, granules were prepared in the same manner as in Experimental Example 6, except that 0.42 mass % of carbon powder was added.
[0045] ·Molding The mixed powder or granules are compressed at 100 kgf / cm 2 The mixture was uniaxially pressed at a pressure of 100 MPa to produce a disk-shaped compact with a diameter of 35 mm and a thickness of approximately 10 mm, which was then placed in a graphite mold for sintering.
[0046] Firing The disk-shaped molded body was hot-pressed and sintered to obtain a ceramic substrate. The pressure in the hot-press sintering was 200 kgf / cm. 2 The mixture was then fired at the firing temperature (maximum temperature) shown in Table 1. The atmosphere was N2 until the end of firing. The firing temperature was maintained for 4 hours.
[0047] [evaluation] (1) Crystal phase evaluation The ceramic substrates obtained in Experimental Examples 1 to 7 were ground in a mortar, and the crystal phases were identified using an X-ray diffractometer. The measurement conditions were CuKα, 40 kV, 40 mA, 2θ = 5 ~ 70 ° A sealed tube type X-ray diffractometer (D8 ADVANCE manufactured by Bruker AXS) was used. As a result, in all of Experimental Examples 1 to 7, the main phase was magnesium-aluminum oxynitride (with a peak at 2θ=47 to 49°). This main phase coincided with the peak of magnesium-aluminum oxynitride identified in Patent Document 1. Figures 5 and 6 show XRD charts of representative examples (Experimental Examples 3 and 5).
[0048] (2) Carbon (C) content The C content was measured in accordance with the method for measuring the total carbon content described in JIS R1616:2007. Specifically, the sample was burned together with a combustion improver in an oxygen stream by high-frequency heating, and the carbon dioxide (and carbon monoxide) produced was sent together with oxygen to an infrared analyzer, and the change in the amount of infrared absorption was measured to determine the C content. Table 1 shows the C contents of the ceramic bases obtained in Experimental Examples 1 to 7. The C contents were 0.002 mass% and 0.30 mass% in Experimental Examples 1 and 7, respectively, but were 0.005 to 0.21 mass% in Experimental Examples 2 to 6. Experimental Example 1 is an embodiment of Patent Document 1, and the C content in Experimental Example 1 is the value when no carbon source was actively added (the C content contained as an impurity).
[0049] (3) Volume resistivity (500℃) The volume resistivity was measured in air at 500°C according to a method in accordance with JIS-C2141. The test piece shape was 50 mm in diameter × (0.5-1 mm), with the main electrode having a diameter of 20 mm, the guard electrode having an inner diameter of 30 mm and an outer diameter of 40 mm, and the application electrode having a diameter of 40 mm, each electrode being formed of silver. The applied voltage was 500 V / mm, and the current value was read 3 minutes after the voltage was applied, from which the room temperature volume resistivity was calculated. The volume resistivities of the ceramic substrates obtained in Experimental Examples 1-7 are shown in Table 2. In the volume resistivities in Table 2, "E8" is 10 8 and "E10" is 10 10 The volume resistivity at 500°C is 1×10 9 The resistivity at 500°C was 1×10 Ωcm or more, whereas the values in Experimental Examples 1 and 7 were lower. A graph showing the relationship between the C content and the volume resistivity at 500°C is shown in FIG. 7. From the graph in FIG. 7, it is clear that the volume resistivity at 500°C was 1×10 9 It can be seen that the C content at which the strain rate exceeds Ωcm is 0.005 to 0.275 mass%. In addition, if the C content is 0.011 to 0.19 mass%, the strain rate is 5×10 9 It is even better if it is Ωcm or more.
[0050] (4) Thermal conductivity (room temperature) The thermal conductivity was measured by a laser flash method. The thermal conductivity at room temperature of the ceramic substrates obtained in Experimental Examples 2, 3, 5, and 6 is shown in Table 2.
[0051] (5) Average coefficient of linear thermal expansion (40 to 1000°C) The average linear thermal expansion coefficient at 1000°C was measured in a nitrogen atmosphere at 40 to 1000°C using a dilatometer (manufactured by Bruker AXS). 1000℃ The average linear thermal expansion coefficients at 1000 MPa are shown in Table 2.
[0052] (6) Etching rate Table 2 shows the etching rates of the ceramic substrates obtained in Experimental Examples 1, 3, 5, and 6. Specifically, the surface of each material was polished to a mirror finish, and a corrosion resistance test was performed under the following conditions using an ICP plasma corrosion resistance tester. The etching rate of each material was then calculated by dividing the step between the masked surface and the exposed surface, measured using a step gauge, by the test time. As a result, it was found that Experimental Examples 3, 5, and 6 had corrosion resistance equal to or greater than that of Experimental Example 1 (the product in Patent Document 1, which has corrosion resistance equal to or greater than that of spinel). ICP: 800W, bias: 300W, introduced gas: NF3 / Ar=75 / 100sccm 13Pa, exposure time: 5h, sample temperature: 550℃
[0053] [Table 1]
[0054] [Table 2]
[0055] [Experimental Examples 8-19] In Experimental Examples 8 to 19, the MgO raw material, the Al2O3 raw material, and the AlN raw material were weighed out so as to obtain the mass% shown in Table 1, and mixed powders or granules were prepared in accordance with Experimental Examples 1 to 7, and then molded and fired to obtain ceramic substrates. The C content of the obtained ceramic substrates was as shown in Table 1. The C content in Experimental Examples 8, 12, and 16 is the value when no carbon source was actively added (the C content contained as an impurity).
[0056] [Experimental Example 20] Experimental Example 20 is an example of a highly thermally conductive substrate made of AlN-YAG. First, the AlN raw material, the Y2O3 raw material, the Al2O3 raw material, and the TiO2 raw material were weighed out to be 74.5, 15, 10, and 0.5 mass%, respectively, and wet-mixed for 4 hours using isopropyl alcohol as a solvent, a nylon pot, and alumina balls with a diameter of 5 mm. After mixing, the slurry was taken out and dried at 110°C in a nitrogen gas flow. Then, it was passed through a 30-mesh sieve to obtain a blended powder. Using this blended powder, molding and sintering were performed in the same manner as in Experimental Example 1 to obtain a disk-shaped highly thermally conductive substrate. When the XRD spectrum of this highly thermally conductive substrate was analyzed, the main phase was AlN-YAG. In addition, the color of the highly thermally conductive substrate was black. The volume resistivity of the obtained highly thermally conductive substrate at 500°C was 5×10 9 Ωcm, thermal conductivity at room temperature is 81 W / m K, 40~ 1000 The thermal expansion coefficient in °C is 6.1 x 10 -6 / K. That is, the thermal conductivity was about 10 times that of Experimental Examples 2, 3, 5, and 6, and the thermal expansion coefficient was equivalent to that of Experimental Examples 2, 3, 5, and 6. Experimental Example 20 can be used as the shaft 28 of the wafer mounting tables 10 to 40 or the highly thermally conductive base 23 of the wafer mounting tables 20 to 40 described above. [Explanation of symbols]
[0057] 10 wafer mounting table, 12 ceramic base, 12a wafer mounting surface, 14 electrostatic electrode, 16 resistance heating element, 18 shaft, 20 wafer mounting table, 22 ceramic base, 22a wafer mounting surface, 23 highly thermally conductive base, 24 electrostatic electrode, 26 resistance heating element, 28 shaft, 30, 40 wafer mounting table.
Claims
1. A ceramic material containing magnesium-aluminum oxynitride, The carbon content is 0.005 to 0.275 mass%; The main phase is a magnesium-aluminum oxynitride phase, which has an XRD peak at least at 2θ = 47 to 50 ° when CuKα radiation is used. High resistance and corrosion resistant ceramic material.
2. Volume resistivity at 500°C is 1×10 9 Ωcm or more, The ceramic material according to claim 1.
3. Contains titanium The ceramic material according to claim 1 or 2.
4. A ceramic base formed of the ceramic material according to any one of claims 1 to 3 and capable of mounting a wafer on its upper surface; An electrode disposed inside the ceramic substrate; A wafer mounting table comprising:
5. A ceramic base formed of the ceramic material according to any one of claims 1 to 3 and capable of mounting a wafer on its upper surface; a highly thermally conductive base provided on a lower surface of the ceramic base and having a thermal conductivity higher than that of the ceramic base; an electrode disposed inside the ceramic base, inside the highly thermally conductive base, or between the ceramic base and the highly thermally conductive base; a resistance heating element disposed inside the highly thermally conductive base and below the electrodes; A wafer mounting table comprising:
6. A ceramic substrate on which a wafer can be placed, the ceramic substrate being formed of a ceramic material containing magnesium aluminum oxynitride and having a carbon content of 0.005 to 0.275 mass %, the ceramic substrate having an upper surface on which a wafer can be placed; a highly thermally conductive base provided on a lower surface of the ceramic base, the highly thermally conductive base having a higher thermal conductivity than the ceramic base and including AlN and YAG; an electrode disposed inside the ceramic base, inside the highly thermally conductive base, or between the ceramic base and the highly thermally conductive base; a resistance heating element disposed inside the highly thermally conductive base and below the electrodes; A wafer mounting table comprising:
7. The highly thermally conductive substrate contains titanium. The wafer stage according to claim 6 .
8. The ceramic material has a volume resistivity of 1 x 10 9 Ωcm or more at 500°C. The wafer stage according to claim 6 or 7.
9. The ceramic material contains titanium. The wafer mounting table according to any one of claims 6 to 8.
10. The ceramic material has a magnesium-aluminum oxynitride phase as a main phase, the XRD peak of which appears at least at 2θ = 47 to 50° when CuKα radiation is used. The wafer mounting table according to any one of claims 6 to 9.
Citation Information
Patent Citations
Blowwoff port structure of air conditioner hanging from ceiling
JP1981080645A
Aluminum nitride ceramics, member for manufacturing semiconductor and anticorrosive member
JP2003221279A
Ceramic substrate for semiconductor manufacturing / inspecting apparatus
JP2004172637A
Ceramic member and manufacturing method therefor
JP2006128603A
Aluminum nitride powder, aluminum nitride-based ceramic sintered body, member for semiconductor manufacturing device, aluminum nitride luminescent material, and method of manufacturing aluminum nitride powder
JP2007191383A